A diagnostic multiplex PCR scheme for identification of plant-associated bacteria of the genus Pantoea - CGIAR Research Program on Rice (2018)
A set of PCR primers that specifically detect each of the three species, P. agglomerans, P. ananatis, and P. stewartii, was designed. A multiplex PCR protocol which can distinguish these three species and also detects members of other Pantoea species was further developed.